Reading Hybridity and Ambivalence in Pramoedya Ananta Toer Novels: a Systematic Literature Review - surtinawati; E. Ngestirosa Endang Woro Kasih (Universitas Muria Kudus, 2026)
This study aims to examine the representation of the concepts of hybridity and ambivalence in the works of Pramoedya Ananta Toer through the Systematic Literature Review (SLR) approach. Drawing on the postcolonial theory of Homi K. Bhabha and using the PRISMA framework and thematic analysis of Braun & Clarke, the study screened and analyzed 14 relevant academic articles. The results of the study show that hybridity in Pramoedya's work is seen through figures such as Minke and Nyai Ontosoroh, who are somewhere between colonial and local cultures, as well as in the use of language and narrative structure. Meanwhile, ambivalence is reflected in characters such as Pangemanann, who portray the moral dilemmas of colonial subjects. In addition, this study also highlights aspects of gender hybridity, colonial trauma in children, and language hegemony in the translation of works. This research found that Pramoedya's work is not only a historical narrative, but also a space to dismantle colonial domination and build a national identity. The. This study also identified gaps in studies that could be further developed, such as spiritual hybridity and minority representation.Â